2005
DOI: 10.1007/s00429-005-0059-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine ultrastructure of chromaffin granules in rat adrenal medulla indicative of a vesicle-mediated secretory process

Abstract: Observation by transmission electron microscopy, coupled with morphometric analysis and estimation procedure, revealed unique ultrastructural features in 25.94% of noradrenaline (NA)-containing granules and 16.85% of adrenaline (A)-containing granules in the rat adrenal medulla. These consisted of evaginations of the granule limiting membrane to form budding structures having different morphology and extension. In 14.8% of NA granules and 12.0% of A granules, outpouches were relatively short, looked like small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, the diameter (180 -220 nm) of these newly formed vesicles was slightly larger than the size (100 -130 nm) of catecholamine storage granules found in our clone of wild-type PC12 cells (Fig. 4), but nevertheless well within the broad diameter range (ϳ30 -330 nm) reported for chromaffin granules in rodents (12,13,41,42).…”
Section: Cga and The Formation Of Dense-core Secretory Organelles Inmentioning
confidence: 71%
“…However, the diameter (180 -220 nm) of these newly formed vesicles was slightly larger than the size (100 -130 nm) of catecholamine storage granules found in our clone of wild-type PC12 cells (Fig. 4), but nevertheless well within the broad diameter range (ϳ30 -330 nm) reported for chromaffin granules in rodents (12,13,41,42).…”
Section: Cga and The Formation Of Dense-core Secretory Organelles Inmentioning
confidence: 71%
“…A variation in density has also been noted, with the highest density of 8 vesicles per um 2 , ascribed to the monkey (335). The vesicles contain various neurochemicals; primarily catecholamines (523) and chromogranin neuropeptides (336) but, presumably also, adenine nucleotides and Ca 2+ (914) giving the type I cell the appearance of adrenal medullary chromaffin cells, albeit that the dense core vesicles in the type I cell may, in most cases, only be up to half as large as their counterparts in the adrenal medulla (176, 319). The small size of the granules and the relative small mass of carotid body tissue, makes quantification of vesicular content difficult, but the use of insulated, carbon electrodes and amperometry with either enzymically dispersed, single, rabbit type I cells (849), or conglomerations of cells in a thin slice rat carotid body preparation (670) has revealed that type I cells from both species secrete catecholamine (presumed to be dopamine), with a single quantal charge of 44 to 46 pC.…”
Section: Cell Types Of the Carotid Bodymentioning
confidence: 99%
“…In mammals, glucocorticoids modulate catecholamine synthesis, storage and secretion; moreover, they have been implicated in chromaffin cell differentiation (Bornstein et al 1997;Hodel 2001;Hiwatashi et al 2002;Yonekubo et al 2003;Laborie et al 2003;Carrasco-Serrano and Criado 2004;Crivellato et al 2006). The activity of the enzyme phenyletanolamine-N-methyl transferase (PNMT), converting norepinephrine (NE) into epinephrine (E), in mammals and other species of Vertebrates, is stimulated by glucocorticoids, which cause the conversion of noradrenergic to adrenergic chromaffin cells (Hodel 2001;Laborie et al 2003).…”
Section: Introductionmentioning
confidence: 99%